THE EFFECT OF INSTITUTIONAL OWNERSHIP, BOARD SIZE, AND INDEPENDENT COMMISSIONER ON FINANCIAL PERFORMANCE - Kristiani, Diana; Ekadjaja, Agustin (Graduate Program of Universitas Tarumanagara, 2025)
This research aims to collect empirical data that will explain the impact that institutional ownership, board size, and independent commissioners have on financial performance, as assessed by return on assets within the banking sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. It is determined by dividing the net profit after taxes by the total assets of the company. The calculation for the institutional ownership variable involves dividing the total number of shares that are outstanding by the number of shares that individual institutions hold. The board size variable is determined by the total number of active board members in the company, whereas the independent commissioner variable is determined by the proportion of independent commissioners to the total number of commissioners in the company. The company's annual report served as the source for the secondary data used in this research and was analyzed using the Microsoft Excel version 2016 application and the SPSS version 25 program. The results of the research show that only the board of directors size variable has a significant effect on the company's financial performance, which is proxied by ROA. Meanwhile, the institutional ownership and independent commissioner variables do not show a significant influence on financial performance.